Optical and dielectric analysis of ZnO nanorods doped polymer dispersed liquid crystal and ethanol gas sensing investigation. Issue 14 (7th December 2020) - Liu, Yourong; Zheng, Jihong; Jiang, Zhipeng; Zhu, Qing; Chen, Qi; Zhuang, Songlin
ABSTRACT: The spectra and dielectric properties of polymer-dispersed liquid crystal films doped with different concentrations of ZnO nanorods were studied. The scanning electron microscopy images show that doping ZnO nanorod concentration can increase the size of liquid crystal droplets to microscale. The absorption spectra of the films also show that the edge of the absorption band of the composite system moves towards high energy with the increase of the concentration of ZnO nanorods. On the other hand, the investigation results show that the dielectric constant and loss increase with the increase of doping concentration from 4 Hz-1 MHz. Further analysis of the Cole–Cole diagram fitted by Havriliak-Negami equation shows that there are three relaxation processes. The improvement of dielectric strength and relaxation frequency of nanocomposites was observed at low frequencies of 100 Hz. A threefold reduce in relaxation time for the doped sample (0.5 wt.%) was obtained compared with that of pure sample without doping. In addition, the studies show that the temperature has a great influence on the activation energy of materials, which have a slight increase ( 5°C) in transition temperature of liquid crystals. Practically, in ethanol gas sensing experiment, the results show the value of permittivity increases and impedance decreases. Graphical abstract Abstract : uf0001